Human Leukocyte Antigens and Epstein–Barr Virus-Associated Nasopharyngeal Carcinoma: Old Associations Offer New Clues into the Role of Immunity in Infection-Associated Cancers - Su, Wen-Hui; Hildesheim, Allan; Chang, Yu-Sun (Frontiers in Oncology, 2013)
Nasopharyngeal carcinoma (NPC) is an Epstein–Barr virus (EBV) associated tumor. In addition to EBV, host genetic factors are believed to be important determinants of NPC risk. Of all genes studies to date, human leukocyte antigen (HLA) genes have shown the most consistent evidence for association with NPC, both from candidate-gene studies and genome-wide association studies (GWAS). In this report we summarize results from recent studies that evaluated the association between HLA and NPC, and discuss whether findings reflect direct causal associations for HLA genes and/or indirect associations that mark causal associations with other genes in the gene-dense major histocompatibility (MHC) region where HLA resides. We also compare GWAS results across cancer sites for which strong hits in the MHC region were observed to generate new hypotheses regarding the role of HLA genes in the development of EBV-associated cancers such as NPC. Of note, we report that MHC associations for EBV-associated cancers (NPC, EBV+ Hodgkin lymphoma) are driven by HLA class I genes. In contrast, MHC associations for other viral-associated cancers (cervical cancer, hepatocellular carcinoma) or other hematopoetic cancers (EBV− Hodgkin lymphoma, leukemia, non-Hodgkin lymphomas) are driven by HLA class II genes, and those for other solid tumors with less clear links to infections (lung, testicular, prostate cancers) are driven by non-HLA genes in the MHC region. Future studies should aim to better understand these patterns.